1992
DOI: 10.1364/ao.31.005121
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of visible and infrared beams by falling snow

Abstract: Classical optics holds that the extinction cross of particles should be equal to twice their geometric cross section, in the limit where the particles are much larger than the wavelength. It follows that the extinction coefficient of such large scatterers should be independent of wavelength. Snowflakes are much larger than the wavelengths of visible and infrared radiation, yet many investigators have found that the visible and infrared extinction coefficient of falling snow measured with transmissometers is wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The fractional error in optical-depth measurements because of light scattered into the finite collection angle of the detector 7 was estimated to be less than 1% for the 0.685-µm wavelength and less yet for the IR. Although snow is well known to scatter by diffraction a nonnegligible amount of energy into typical detectors, [7][8][9] the fractional amount of light scattered into typical detectors is much less for the comparatively much smaller particle laboratory icecloud scatter. 15 The fractional error in underestimation of extinction measurements scales as the product 1single-scatter albedo D 2 l 22 2 so that IR measurements are less error prone than are visible measurements for comparable source and detector dimensions.…”
Section: A Cloud Chamber and Optical Arrangementmentioning
confidence: 99%
See 2 more Smart Citations
“…The fractional error in optical-depth measurements because of light scattered into the finite collection angle of the detector 7 was estimated to be less than 1% for the 0.685-µm wavelength and less yet for the IR. Although snow is well known to scatter by diffraction a nonnegligible amount of energy into typical detectors, [7][8][9] the fractional amount of light scattered into typical detectors is much less for the comparatively much smaller particle laboratory icecloud scatter. 15 The fractional error in underestimation of extinction measurements scales as the product 1single-scatter albedo D 2 l 22 2 so that IR measurements are less error prone than are visible measurements for comparable source and detector dimensions.…”
Section: A Cloud Chamber and Optical Arrangementmentioning
confidence: 99%
“…Single-scattering contributions were sufficient to explain the main features of the extinction measurements in snow for optical depths less than unity. 8 Reference 8 also shows the calculated effect of multiple scattering on a 0.633-µm laser beam captured completely by the detector. Figure 13 of Ref.…”
Section: A Cloud Chamber and Optical Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxiliary lights mounted away from the operator's direct line of sight (i.e., on the passenger side) reduced back-reflected light and eye discomfort [37][38][39]. Additionally, narrow beam light (i.e., spot lights) produced less back-reflected light compared to wide beams of light [40,41].…”
Section: Visibility and Fatiguementioning
confidence: 99%
“…Auxiliary lights should be placed outside of the snowplow operator's line of sight (i.e., locate lights on the passenger side of the vehicle) [37][38][39]. Exterior lights should have narrow-beam spread bulbs (i.e., spot lights) [39][40][41]. Some research suggested that longer wavelength light (e.g., amber and red) reduced the amount of reflected light from warning lights; however, the effects from light color were limited compared to placement and beam spread [36].…”
Section: Visibility-related Equipmentmentioning
confidence: 99%